Effects of heat treatment and visible light exposure on the oxidative stability of rice bran and of rice bran oil - Kim, Mi-Ja; Park, Jung Woo; Kim, Ji Young; Park, Kye Won; Lee, Sang-Jun; Jang, Jae-Kweon; Lee, Jae Hwan (Food science and biotechnology, 2013)
Rice bran was heated at 120°C for 0 to 30 min to extend the oxidative stability. Also, effects of visible light irradiation on the crude rice bran oil (RBO) from rice bran heated at 120°C for 20 min were studied. As heat treatment time increased from 0 to 30 min, rice bran had significantly high oxidative stability at 40°C for 12 days ( p <0.05). Headspace oxygen content in rice bran without heat treatment decreased significantly ( p <0.05) whereas those in heat treated rice bran did not change significantly ( p >0.05). Results of acid value and conjugated dienoic acid (CDA) confirmed the higher oxidative stability of heat treated rice bran. γ-Oryzanol content was not significantly different among crude RBO during heat treatment and storage ( p >0.05). Visible light irradiation caused similar degree of lipid oxidation in crude RBOs from rice bran irrespective of heat stabilization for 48 h, which may be due to the presence of photosensitizers in crude RBO like chlorophylls. This study showed that heat treatment was not effective to enhance the oxidative stability of RBO under visible light irradiation and products containing rice bran should be stored in the dark conditions.